Research on the function of the Cend1 regulatory mechanism on p75NTR signaling in spinal cord injury. (October 2022) - Chen, Chen; Yu, Qin; Huang, Yunsheng; shen, Xiao-Qin; Ding, Zhen-Zhong; Chen, Gui-Wen; Yan, Jun; Gu, Qing-Guo; Mao, Xingxing
Abstract: How to use NSC repair mechanisms, minimize the loss of neurons, and recover the damaged spinal cord functions are hotspots and difficulties in spinal cord injury research. Studies have shown that Cend1 signaling is involved in regulating the NSC differentiation, that p75NTR signaling is involved in the regulation of mature neuronal apoptosis and that NSC differentiation decreases mature neuron apoptosis. Our research group found an interaction between Cend1 and p75NTR, and there was a correlation with spinal cord injury. Therefore, we speculate that Cend1 regulates p75NTR signals and promotes the differentiation of NSCs, and inhibits neuronal apoptosis. Therefore, this study first analyzed the expression of p75NTR and Cend1 in spinal cord injury and its relationship with NSCs and neurons and then analyzed the regulatory mechanism and the mechanism of survival on neuronal apoptosis and differentiation of NSCs. Finally, we analyzed the effect of p75NTR and the regulation of Cend1 damage on functional recovery of the spinal cord with overall intervention. The completion of the subject will minimize the loss of neurons, innovative use of NSC repair mechanisms, and open up a new perspective for the treatment of spinal cord injury. Graphical abstract: Unlabelled Image